PENGARUH DESAIN PRODUK DALAM KEPUTUSAN PEMBELIAN KONSUMEN - Cokorda Istri Mas Kusumaningrat (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2020)
Basically the needs and desires of consumers always change and even tend to increase from time to time so the company needs to conduct a marketing research in an effort to find out what products are actually needed and desired by consumers. This condition encourages companies to carry out product design strategies in accordance with consumer desires. The purpose of this research is to find out how the product design in consumer purchasing decisions and their benefits to increasing sales volume. The process of data analysis in this study using Moleong’s theory is to organize and sort data into patterns, categories and basic units of description so that themes can be determined and work hypotheses can be found as suggested by the data. The results of the study, showed that product design in consumer purchasing decisions on Unique Leather Design is to prioritize different display designs that are sold in the market and maintain the quality of the product. Conclusion of the results of the study, designs that are of interest to consumers Unique Leather Design is an attractive design that prioritizes quality. And in the future use a strategy that increases the amount of production.